HUBUNGAN TINGKAT PENGETAHUAN PASIEN DIABETES MELLITUS TENTANG PENYAKIT DAN DIET DENGAN KEPATUHAN DALAM MENJALANKAN DIET DIABETES MELLITUS - TRIANA, RIZA '; Karim, Darwin '; Jumaini, Jumaini ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this study was to determine The Correlation level of knowledge about disease DM patient and diet with dietary adherence in DM run. This study used a descriptive study with cross-sectional design. The study was conducted at the Petala Bumi hospital with 33 respondents. The sampling method used is accidental sampling. Measuring instruments used in this study is a questionnaire that has been tested for validity and reliability. Analysis that was used is univariate and bivariate analysis with chi-square test. Result of this research has shown that from 15 respondent (45,5% of total sampel) with low level of knowledge and has not obedient are 10 respondents (71,4%), while from 18 respondents with hight level of knowledge  with degrees of significance 0,05 obtained the pv (0,027) < α (0,05) and OR point 7,000. It means that there is correlation between patients level of knowledge about the disease and meal planning with diabetes mellitus diet adherence with 7,000 greater obedient from hight level of knowledge. The results of this study can recommend the nurse to be active in providing health education programs (health education) related increase patients' knowledge about the disease and diet compliance in carrying diet Diabetes Mellitus. Keywords: diet, DM, knowledge, obedience